A review on the recent progress, challenges, and perspectives of atmospheric‐pressure cold plasma for preparation of supported metal catalysts. Issue 5 (23rd March 2018) - Di, Lanbo; Zhang, Jingsen; Zhang, Xiuling
Abstract : Supported metal catalysts are of great importance in energy and environmental applications. Atmospheric‐pressure (AP) cold plasma, generally generated by dielectric barrier discharge and cold plasma jet, has been proved to be a fast, facile, and energy efficient method for fabricating supported metal catalysts. In this review, the recent progress, challenges, and perspectives of AP cold plasma for synthesizing supported metal catalysts are discussed. Focus is placed on recent work demonstrating the discharge types of AP cold plasma, and the characteristics of the synthesized supported metal catalysts. The reduction mechanism of AP cold plasma is also discussed in light of several possible mechanisms that have been proposed in previous work. Abstract : Atmospheric‐pressure (AP) cold plasma technique for synthesizing supported metal catalysts has been reviewed. The discharge types of AP cold plasma, and the characteristics of the synthesized supported metal catalysts have been summarized and discussed. The reduction mechanism has also been discussed, and the challenges and perspectives are proposed.